Animals, Relations, and the Laissez-Faire Intuition. (August 2016) - Hedberg, Trevor
In Animal Ethics in Context, Clare Palmer tries to harmonise two competing approaches to animal ethics. One focuses on the morally relevant capacities that animals possess. The other is the Laissez-Faire Intuition (LFI): the claim that we have duties to assist domesticated animals but should (at least generally) leave wild animals alone. In this paper, I critique the arguments that Palmer offers in favour of the No-Contact LFI – the view that we have ( prima facie ) duties not to harm wild animals but no duties to assist them. I argue that Palmer's endorsement of the No-Contact LFI is unwarranted. Her arguments actually provide strong reasons to endorse what I call the Gradient View – a position that posits weak presumptive duties to assist wild animals that become stronger as our relations with the animals grow stronger.